Heuristics in philosophy - Williamson, T (Springer Netherlands, 2024)
This article argues that heuristics play a key role in philosophy, in generating both our verdicts on proposed counterexamples to philosophical theories and philosophical paradoxes. Heuristics are efficient ways of answering questions, quick and easy to use, but imperfectly reliable. They have been studied by psychologists and cognitive scientists such as Gigerenzer and Kahneman, but their relevance to philosophical methodology has not been properly recognized. Several heuristics are discussed at length. The persistence heuristic can be summarized in the slogan ‘Small changes don’t matter’. Without it, updating would present an intractable problem for both natural and artificial intelligence. But our reliance on the persistence heuristic also makes us vulnerable to paradoxes of vagueness. Disquotational heuristics of various kinds are considered. They play central roles in our ascriptions of truth, falsity, and belief, but they also generate semantic paradoxes such as the Liar and Frege puzzles about coreference. The use of an additive heuristic for combining reasons is also discussed. Our reliance on fallible heuristics in philosophy does not make philosophical knowledge impossible, just as our reliance on fallible heuristics in perception does not make perceptual knowledge impossible. Nevertheless, it should motivate us to take a more critical attitude to our data. By identifying and analyzing the heuristics on which we rely, we may be able to work out where they make us most vulnerable to error.